ESTIMATION, REALITY AND TREND OF GROUNDWATER NITRATE CONCENTRATION UNDER UNSEWERED AREA OF YOGYAKARTA CITY – INDONESIA - Doni Prakasa Eka Putra (Journal of Applied Geology, 2015)
In the last two decades, urbanization has transformed Yogyakarta City expanding beyond its administrative area with about one million inhabitants. The City sited on shallow unconfined aquifer has rapidly changed without appropriate access to sanitation and piped water supply. Until now, only 9% of the urban population is served by sewers system and less than 30% of urban population have access to clean water which supplied by the local public water-work. Most of the urban population depend on shallow groundwater for much of their water supply. Regards to the massive used of on-site sanitation systems in the city, contamination of nitrate in shallow groundwater is predicted to occur and surveys of domestic dug wells have revealed a widespread nitrate contamination of the groundwater. Comparison of groundwater nitrate and chloride concentration from several old data and the latest data shows clearly an evidence of the increasing of nitrate concentration and nitrate leaching in the shallow groundwater under Yogyakarta City overtime. Considering the trend, it is no doubt that most of nitrate concentration under urbanized area in the Yogyakarta City will be greater than 50 mg/L in the next several years, if appropriate management action to deal with the on-site sanitation system is not conducted.